2023
DOI: 10.3390/su15065248
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Influence of Urban Park Landscape Features on Visitor Behavior

Abstract: The relationship between visitor behavior and the park landscape is complex. Influences of some park features on visitor behavior are unconfirmed and change with time and space, which always confuses landscape architects and park managers. These spatiotemporal dependent effects were less studied. To understand this influence, an empirical study was conducted in 10 representative parks across the West Lake Scenic Area in Hangzhou, China. A system for Observing Play and Recreation in Communities was applied to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We speculated that the users of large integrated parks and country parks, such as the Hangzhou Westlake Scenic Area, are mainly from outside of this region, which provided less health benefits to local residents. Another reason is that the large and dense GS would reduce the willingness of local users to physically exercise, especially single visitors who consider potential criminal risks [43,44]. European studies also supported that neighboring GS was better for the health of local residents than the total GS amount in the city, and reduced the natural-cause and suicide mortality [45,46].…”
Section: Landscape Configuration Of Gs Affected Mortalitymentioning
confidence: 99%
“…We speculated that the users of large integrated parks and country parks, such as the Hangzhou Westlake Scenic Area, are mainly from outside of this region, which provided less health benefits to local residents. Another reason is that the large and dense GS would reduce the willingness of local users to physically exercise, especially single visitors who consider potential criminal risks [43,44]. European studies also supported that neighboring GS was better for the health of local residents than the total GS amount in the city, and reduced the natural-cause and suicide mortality [45,46].…”
Section: Landscape Configuration Of Gs Affected Mortalitymentioning
confidence: 99%
“…Specifically, landscape design influences user experience and soundscape perception by enhancing visual experience and functions as noise masking effect and create positive sounds [59]- [61]. Landscape features influence visitor's behaviour pattern depending on their contexts such as landmarks serving as gathering points and the effect of vegetation cover varies among the visitors [62]. The design of social space in a park also encourages planned behaviors in the park allowing spaces for leisure and social activities such as singing and dancing [62] which encourages a variety of sounds and influence the expectations of the users in the parks.…”
Section: Limitation and Scope For Further Studiesmentioning
confidence: 99%
“…Landscape features influence visitor's behaviour pattern depending on their contexts such as landmarks serving as gathering points and the effect of vegetation cover varies among the visitors [62]. The design of social space in a park also encourages planned behaviors in the park allowing spaces for leisure and social activities such as singing and dancing [62] which encourages a variety of sounds and influence the expectations of the users in the parks. As the four different study area in this research have different park designs which impacts the patterns of movement and preferred areas within the park, it is suggested that future research can further consider comparing the soundscape perception of parks with similar design intention or to deeply compare different planned areas within a park to explore how far does the design of the park influences the soundscape perceptions.…”
Section: Limitation and Scope For Further Studiesmentioning
confidence: 99%
“…Yet, European countries have different approaches, such as the Spanish MESMIS (productivity, stability, reliability, resilience, adaptability, equity, and self-reliance) [28]. Based on this method and different studies in the literature, it was thought that a sustainable urban park should have the following 10 features [1,10,[28][29][30][31] When designing an outdoor therapy garden, it is important to experience nature with a combination of texture, taste, color, light, and sound [32]. For public open green spaces to appeal to most, if not all, of these 5 senses for relaxation and rehabilitation, it is necessary to analyze these urban areas' strengths, weaknesses, opportunities, and threats.…”
Section: Introductionmentioning
confidence: 99%